Post-Mastectomy Radiotherapy Involving Supraclavical Nodes – Matchline Dose, Tumour Dose And Organs At Risk Dose - Alzoubi, Ahmad Saleem Salem (2009)
The purposes of this study were investigated the effect of the overlap resulting from the beam divergence of the tangential fields onto a supraclavicular field in breast irradiation of patients undergoing breast radiotherapy, to examine the absorbed dose to the skin of patients in such treatments. Tujuan kajian ini ialah untuk menyelidiki kesan pertindihan akibat daripada pencapahan alur medan tangen terhadap medan supraklavikal dalam penyinaran payu dara pesakit yang menerima rawatan radioterapi payu dara, meneliti dos terserap dalam kulit pesakit untuk rawatan tersebut